Pengabdian kepada pelajar SMA Muhammadiyah: Pengembangan kreativitas melalui inovasi kuliner berbasis limbah domestik - Inayah, Astrina Nur; Aksan, Muhammad; Haryono, Iranita (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2025)
This community service program was conducted at Muhammadiyah High School to develop student creativity through waste-based culinary innovations, as a solution to students' limited understanding of organic waste utilisation and the lack of entrepreneurial activities within the school environment. The partners faced several challenges, including low awareness of the importance of recycling and a lack of practical skills in creating marketable products. This activity was implemented through participatory training methods, interactive discussions, and hands-on practice in processing household organic waste—such as fruit peels and vegetable scraps—into innovative culinary products, such as carrot peel dim sum, dragon fruit peel ice cream, and banana peel soy sauce. Throughout the process, students were actively involved, from planning, production, and packaging, with simple entrepreneurship materials provided. The results of the activity showed a significant increase in students' knowledge of waste management and entrepreneurial skills, marked by high enthusiasm, the creation of several creative culinary products, and students' plans to sell their products at the school bazaar. In conclusion, this program successfully fostered environmental awareness and an entrepreneurial spirit among students through a creative and applicable approach relevant to their daily lives.